9 * ☐ : 6 = 6
8 * ☐ : 4 = 10
30 : ☐ * 8 = 40
18 : 9 * ☐ = 40
36 : 6 * ☐ = 60
56 : 8 + ☐ = 100
9 * 4 : 6 = 6
8 * 5 : 4 = 10
30 : 6 * 8 = 40
18 : 9 * 20 = 40
36 : 6 * 10 = 60
56 : 8 + 93 = 100
Вычисления
9 * ☐ : 6 = 6
9 * ☐ = 6 * 6
9 * ☐ = 36
☐ = 36 : 9
☐ = 4
8 * ☐ : 4 = 10
8 * ☐ = 10 * 4
8 * ☐ = 40
☐ = 40 : 8
☐ = 5
30 : ☐ * 8 = 40
30 : ☐ = 40 : 8
30 : ☐ = 5
☐ = 30 : 5
☐ = 6
18 : 9 * ☐ = 40
2 * ☐ = 40
☐ = 40 : 2
☐ = 20
36 : 6 * ☐ = 60
6 * ☐ = 60
☐ = 60 : 6
☐ = 10
56 : 8 + ☐ = 100
7 + ☐ = 100
☐ = 100 − 7
☐ = 93